Intellectual property in the economic performance of Venezuela (Gestión y Gerencia, 2020)
Promoters of development and creativity must be recognized and respected through the preservation of the creative and inventive processes and granting the author the protection of his rights as owner. This is an incentive that promotes research, cultural progress, scientific advance and technological development, which guarantees in the long term, technological advances and an adequate socio-economic development. The objective is to analyze the behavior of Intellectual Property in Venezuela and the protection rights registries in the last ten years. The research is analytical with non-experimental deductive method; the technique is observation, having as a collection tool a statistical observation guide from the World Intellectual Property Organization (WIPO) and the statistics of the Intellectual Property Autonomous Service (SAPI) in the period between 2007-2017. It is concluded that the trademark registration during the ten years shows the importance of this type of protection for economic and cultural development; concerns the low number of patent registrations and the non-granting of patent certificates since 2002 because it does not encourage the inventiveness development, encourages protection outside the country and low national technological indicators
Keywords: Intellectual Property; trademark; patent; WIPO; SAPI; IPRI; IPR